Mango Agribusiness Development Strategy For Sustainable Agriculture In Karanganyar - Faisal Reza HATAMI; Kusnandar KUSNANDAR; Mohamad HARISUDIN (International Journal of Environmental, Sustainability, and Social Science, 2022)
An agrarian country prioritizes the agricultural sector as its resource because it provides a high and influential contribution to the community, Indonesia is one of a country that has abundant natural resources and its economy depends on the agricultural sector. One of the industries that have the potential to be developed in the plantation sector and can be an aspect of sustainable agriculture is the mango fruit industry. It is necessary to analyze network factors affecting the production of mangoes in Indonesia and provide recommendations and priorities for strategies with the Analytic Network Process to develop sustainable agriculture. Informants are people who come from research locations and are considered the most competent. Priority Alternative strategies obtained by in-depth interviews with experts and processed through the super decision application are Developing Production through Postharvest Training and Improving Facilities (0.331522). These priorities are directly proportional to sustainable agricultural activities, pre-and post-harvest activities that are expected to support and contribute to increasing agricultural productivity profits in the long term, improving environmental quality (not damaging the environment), and as well as welfare of farmers with adequate facilities.